Topographical mapping of metabolic abnormalities in multiple sclerosis using rapid echo-less 3D-MR spectroscopic imaging at 7T - Eva Niess; Assunta Dal-Bianco; Bernhard Strasser; Fabian Niess; Lukas Hingerl; Beata Bachrata; Stanislav Motyka; Paulus Rommer; Siegfried Trattnig; Wolfgang Bogner (NeuroImage)
Objectives: To assess topographical patterns of metabolic abnormalities in the cerebrum of multiple sclerosis (MS) patients and their relationship to clinical disability using rapid echo-less 3D-MR spectroscopic imaging (MRSI) at 7T. Materials and Methods: This study included 26 MS patients (13 women; median age 34) and 13 age- and sex-matched healthy controls (7 women; median age 33). Metabolic maps were obtained using echo-less 3D-MRSI at 7T with a 64 × 64 × 33 matrix and a nominal voxel size of 3.4 × 3.4 × 4 mm³ in an 8-minute scan. After spatial normalization, voxel-wise comparisons between MS and controls were conducted to identify clusters of metabolic abnormalities, while correlations with clinical disability were analyzed using Expanded Disability Status Scale (EDSS) scores. Results: Statistical mapping (FWE-corrected; P<.05) revealed elevated myo-inositol to total creatine (mI/tCr) ratios in the bilateral periventricular white matter and reduced N-acetylaspartate to total creatine (NAA/tCr) within and beyond lesions, notably near the lateral ventricles, cingulate gyrus, and superior frontal gyrus. Patients with sustained disability (EDSS≥2) showed additional reductions in the posterior parietal lobe. A strong negative association was found between NAA/tCr and EDSS in the precentral gyrus (Spearman's rank ρ=-0.58, P=.005), and a moderate positive association between mI/NAA and EDSS in the precentral and superior frontal gyri (ρ=0.47, P=.015). Conclusions: This study highlights the ability of 3D-MRSI at 7T to map widespread metabolic abnormalities in MS, with NAA reductions in prefrontal, motor, and sensory areas, linked to neuroaxonal damage and disability progression, and elevated mI in periventricular regions, reflecting gliosis.